Ecosystem services research: From golden era to next crossing. Issue 1 (March 2023) - Peng, Jian; Xia, Pei; Liu, Yanxu; Xu, Zihan; Zheng, Huining; Lan, Tianhan; Yu, Shuying
Ecosystem services has been widely explored in various theoretical or practical studies since its emergence more than 20 years ago. The two big issues in the past golden era of ecosystem services research were: ecosystem services valuing and ecosystem services trade-offs. We analyzed advantages of ecosystem services in promoting the attention that government and the public pay to the natural capital and the management of ecosystem services, together with summarizing the shortcomings. It was found that ecosystem services valuing made the public aware of the importance of natural capital from an economic perspective, while ecosystem services trade-offs highlighted the relationship between various ecosystem services from an ecological perspective, which could be better applied to ecosystem services-based ecosystem management. With an increasing number of papers focusing on ecosystem services flows, it is believed that ecosystem services flows integrating ecology, economy, sociology and geography disciplines will become a new key direction after ecosystem services valuing and trade-offs. To further promote the study of ecosystem services flows that link human and nature within geographical context, we need to focus on the value of ecosystem services flows with payment and benefit accounting, the relationship of ecosystem services flows by trade-off and synergy analysis, and the direction of ecosystem services flows by spatial and temporal assessment. In addition, a more efficient and widely recognized method is also essential for the development of quantifying ecosystem services flow. This study contributes to understanding the development stage of ecosystem services research and highlights the importance of ecosystem services flow research.